Doing Inventing in the Library. Analyzing the Narrative Framing of Making in a Public Library Context - Gro Skåland; Hans Christian Arnseth; Palmyre Pierroux (MDPI AG, 2020)
In this article, we examine how creative making is framed in a public library setting. We pursue this topic by focusing on the trajectory of a group participating in "The Inventor Course" during a school trip to a library. Video recordings of the maker activity comprise the primary data for analysis, supplemented by ethnographic notes. Analysis of the group's interactions shows how different frames for inventing are acted out and intersect during the activity. We describe these frames as inventing as invention, inventing as exploration and inventing as narrative. Findings indicate that a narrative frame is a fruitful approach to making in a library setting and that narratives performed in dialogue with children help them to make sense of their explorations.